The Physical Fitness Level of College Students Before and After Web-Based Physical Education During the COVID-19 Pandemic - Xia, Wei; Huang, Cai-hong; Guo, Yu; Guo, Min-gang; Hu, Ming; Dai, Jian; Deng, Cheng-hu (Frontiers in Pediatrics, 2021)
Background: The COVID-19 pandemic has been an emergency worldwide. Web-based physical education is a choice for college students to keep on their study. The aim of this study was to compare the data of physical fitness of college students before and after web-based physical education. Methods: All the students of 2018 and 2019 in Wuhan University of Technology who had taken the web-based physical education class in 2020 were included in this study. The records of annual physical fitness tests of all the subjects in 2019 and 2020 which were carried out in September were reviewed, including weight, height, body mass index (BMI), vital capacity (VC), 50-m dash, sit-and-reach, standing long jump, male-specific pull-ups and 1,000-m race, and female-specific sit-ups and 800-m race. Results: There were 24,112 male and 9,690 female records of physical fitness tests included in our study. The results of 11,219 male and 4,651 female students who completed both physical fitness tests in 2019 and 2020 were employed for Wilcoxon signed-rank test. Declined performance was observed on male 50-m dash by 0.1 s, male 1,000-m race by 14 s, and female 800-m race by 11 s. Notably, the percentage of male obesity, based on BMI, rose from 10.6 to 15.2% and 17.1 to 21.8% for male overweight; correspondingly, the percentage of male normal weight declined from 55.9 to 51.9% and 16.4 to 11.1% for male thinness. The trend of increasing BMI in males should be paid attention to. Improved results on vital capacity, sit-and-reach, standing long jump for both males and females, female 50-m dash, female sit-ups, and male pull-ups were observed in 2020. All the results of physical fitness tests were significantly different between 2019 and 2020 (p < 0.01) by Wilcoxon signed-rank test. Conclusions: The changes of physical fitness tests before and after web-based physical education suggested that the focus should be placed on improvement for running tests through appropriate alternatives, such as fast running in place and shuttle run. In addition, the simple, convenient, and practical sport that require available equipment and little field should be considered for web-based physical education.